Improvement of the pattern of new services development - Bivainis, Juozas; Drejeris, Rolandas (Business: Theory and Practice, 2006)
This article reviews alternative approaches to new product development and new service development. The distinctions between products and services were recognized and mentioned in the article. The pattern of new service development must be different from the pattern of new product development because of special features of services. When compared with the field of new product development, research into new services has seen fewer developments and offers less comprehensive insights. Giving very limited research into new services development patterns, this section also reviews the patterns and evidence of new product development in order to draw a richer perspective of the question. Original modification of the pattern of new services development is introduced at the end of the article. The pattern consists of six functional components: the determination of new services expedience, new services design, analysis, planning, com- mercialization and evaluation of the implemention of new services. The purpose of all components is argued and commented in the purport of the article. The efficiency of the offered pattern is in the adequacy to the exceptional features of services, in its flexibility to use, which can be self-actualized in two ways: possibility to bypass some stages of the new services development, which are not so purposeful to make. Purposefulness depends on concrete situations. The other way is the possibility to make the work in parallel in some stages. These possibilities depend on concrete situations too. Article in Lithuanian. Naujų paslaugų įdiegimo modelio tobulinimas Santrauka. Straipsnyje pristatoma originali naujų paslaugų įdiegimo modelio modifikacija. Modelį sudaro šeši funkciniai komponentai: naujų paslaugų diegimo tikslingumo nustatymas, naujos paslaugos sumanymas, analizė, projektavimas, komercializavimas ir įdiegimo vertinimas. Argumentuota kiekvieno komponento paskirtis ir atskleistas turinys. Siūlomo modelio efektyvumas - tai gebėjimas atitikti išskirtines paslaugų savybes ir taikymo lankstumas, kuris gali pasireikšti dviem būdais: galimybe aplenkti tuos naujų paslaugų įdiegimo etapus, kai numatytus darbus atlikti nėra tikslinga, atsižvelgiant į konkrečią situaciją, pirmiausia į paslaugos pobūdį ir ją diegiančios įmonės specifiką; galimybe vienu metu etapais vykdyti tam tikrus darbus. Pagrindiniai žodžiai: paslaugų verslas, naujas produktas, naujos paslaugos, įdiegimo organizavimas, įdiegimo modelis, modelio komponentai.